Pengaruh Karakteristik Dewan Pengawas Syariah terhadap Tingkat Financial Soundness Bank Syariah di Indonesia Tahun 2015-2019 - Suci Oktamirza; Vanica Serly (Universitas Negeri Padang, 2021)
This study aims to examine the effect of Shari’ah Supervisory Board characteristics on financial soundness of Islamic banks in Indonesia. This research was conducted by quantitavie method and used data of Islamic banks listed in Financial Service Authority of Indonesia (OJK) at 2015-2019. Total sample was 13 islamic banks for each period. This research used RGEC method as main and newest measurement financial soundness of Indonesian banks. This research also used CAMEL method and Z-Score method as a robustness or additional test. Characteristics of Shari’ah Supervisory Board in this research represented by board size, multi-position, board education levels and meeting frequency.The result of this this study conclude that board size only affects financial soundness of Islamic banks from GCG mechanism and Cash Adequacy Ratio aspects. And multi positions of board will affects financial soundness of Islamic banks from Non Performing Financing, Return On Assets and Operational Expense Toward Operational Income aspects. While, board education levels didn’t have any significant impact on financial soundness of Indonesian Islamic banks in every aspects of RGEC method. And the meeting frequency only affects financial soundness of Indonesian Islamic banks from Operational Expense Toward Operational Income aspects. CAMEL method as the first robustness test showed that all of Shariah Supervisory Board characteristics didn’t have any significant impact on financial soundness of Indonesian Islamic banks while, the Z-Score as the second additional test found that only multi position which was give a significant impact on financial soundness of Indonesian Islamic banks.